2019
DOI: 10.1111/mec.15120
|View full text |Cite
|
Sign up to set email alerts
|

Lineage specific histories of Mycobacterium tuberculosis dispersal in Africa and Eurasia

Abstract: Mycobacterium tuberculosis ( M.tb ) is a globally distributed, obligate pathogen of humans that can be divided into seven clearly defined lineages. An emerging consensus places the origin and global dispersal of M.tb within the past 6,000 years: identifying how the ancestral clone of M.tb spread and differentiated within this timeframe is important for identifying the ecological drivers of the current pandemic. We used Bayesian phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
81
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 65 publications
(137 reference statements)
19
81
5
1
Order By: Relevance
“…A calibrated maximum clade credibility (MCC) tree was generated for the BDSKY+UCLD model, with 3683 years before present (BP) (95% highest posterior density [95% HPD] interval: 2253 – 5821 BP) as an estimated date of emergence for the MTBC (Figure 3a). Tree topology agrees with previously presented phylogenetic analyses of the full MTBC (3,5,37). A birth-death skyline plot illustrates the flux in the effective reproduction number (R) over time (Figure 3b).…”
Section: Resultssupporting
confidence: 88%
“…A calibrated maximum clade credibility (MCC) tree was generated for the BDSKY+UCLD model, with 3683 years before present (BP) (95% highest posterior density [95% HPD] interval: 2253 – 5821 BP) as an estimated date of emergence for the MTBC (Figure 3a). Tree topology agrees with previously presented phylogenetic analyses of the full MTBC (3,5,37). A birth-death skyline plot illustrates the flux in the effective reproduction number (R) over time (Figure 3b).…”
Section: Resultssupporting
confidence: 88%
“…This is interesting as the MAF lineages, MTB L1 and L3 lineages all reportedly grow relatively slower than the MTB L2 and L4 lineages (14, 65, 83, 84, 107). We postulate that the slower growth rate of these lineages and the convergence we observe in their metabolic pathways, may be linked to their similar migration and dispersal patterns in Africa and Eurasia (108), where L2 and L4 have become widely dispersed, while L5, L6, and L7, had more geographically restricted expansion, adapting to more specific hosts. This may have influenced niche adaptation, where L2 and L4, in line with increased dispersion and range expansion, also increased their replicative/growth capacity and ability to transmit, while the more host restricted lineages maintained a lower replicative/growth potential in line with expansion in situ.…”
Section: Resultsmentioning
confidence: 81%
“…Recent analyses point towards the evolutionary rate defined by Bos et al (Bos et al, 2014) as being the most plausible to explain the trajectory of MTBC (Menardo et al, 2019; O’Neill et al, 2019). Our posterior Bayesian estimate indicates that the time of the most recent common ancestor (MRCA) for extant M. bovis lineages is 430 - 2,394 years BP (Before Present) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…We should not neglect the fact that the world saw a demographical explosion and a deep connection between different cultures and communities during the Ancient Roman period (Jongman, 2012; Hanson et al, 2017). It has been suggested that this demographic explosion and economic rise greatly contributed to the spread of human TB worldwide, with naïve human populations from rural areas being exposed to the disease when moving to larger cities (Herzog, Basel, 2003; O’Neill et al, 2019). The economical flourishing was followed by a steep rise in agriculture and livestock capacity (Jongman, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation